A prognostic score to identify low‐risk outpatients with acute deep vein thrombosis in the upper extremity. (15th June 2015) - Rosa‐Salazar, V.; Trujillo‐Santos, J.; Díaz Peromingo, J. A.; Apollonio, A.; Sanz, O.; Malý, R.; Muñoz‐Rodriguez, F. J.; Serrano, J. C.; Soler, S.; Monreal, M.; the RIETE Investigators; Decousus, H.; et al.
Summary Background No studies have identified which patients with upper‐extremity deep vein thrombosis (DVT) are at low risk for adverse events within the first week of therapy. Methods We used data from Registro Informatizado de la Enfermedad TromboEmbólica to explore in patients with upper‐extremity DVT a prognostic score that correctly identified patients with lower limb DVT at low risk for pulmonary embolism, major bleeding, or death within the first week. Results As of December 2014, 1135 outpatients with upper‐extremity DVT were recruited. Of these, 515 (45%) were treated at home. During the first week, three patients (0.26%) experienced pulmonary embolism, two (0.18%) had major bleeding, and four (0.35%) died. We assigned 1 point to patients with chronic heart failure, creatinine clearance levels 30–60 mL min−1, recent bleeding, abnormal platelet count, recent immobility, or cancer without metastases; 2 points to those with metastatic cancer; and 3 points to those with creatinine clearance levels < 30 mL min−1. Overall, 759 (67%) patients scored ≤ 1 point and were considered to be at low risk. The rate of the composite outcome within the first week was 0.26% (95% confidence interval [CI] 0.004–0.87) in patients at low risk and 1.86% (95% CI 0.81–3.68) in the remaining patients. C‐statistics was 0.73 (95% CI 0.57–0.88). Net reclassification improvement was 22%, and integrated discrimination improvement was 0.0055. Conclusions Using six easily available variables, we identified outpatients with upper‐extremity DVT at low risk for adverse events within the first week. These data may help to safely treat more patients at home.